Pd‐Polypyrrole Nanocomposite in Environmentally Friendly Synthesis of Vinylnitriles Using K4Fe(CN)6. Issue 16 (24th April 2018) - Magdesieva, Tatiana V.; Nikitin, Oleg M.; Polyakova, Olga V.; Sazonov, Petr K.; Zolotukhina, Ekaterina V.; Gor'kov, Konstantin V.; Samarov, Alexander V.; Vorotyntsev, Mikhail A.
Abstract: An efficient cyanation of vinyl bromides, activated chlorides and mesylates with K4 Fe(CN)6 has been performed using palladium polypyrrole nanocomposite. The reactions are clean and high yielding. They are highly stereoselective furnishing ( E )‐nitriles from ( E )‐halides and Z ‐nitriles from Z ‐halides. Chemoselective cyanation of sp 2 (vinyl)‐Br bond in the presence of sp 2 (aryl)‐Br is possible. The additional advantages offered by the suggested catalytic system are operational simplicity and the environmentally friendly synthetic methodology (no toxic ligands and the possibility to use environmentally benign aqueous solutions). The catalyst is active under heating and under MW irradiation; it can be reused at least three times. Abstract : Efficient cyanation of vinyl bromides, chlorides and mesylates with K4 Fe(CN)6 has been performed using palladium polypyrrole nanocomposite which is active under heating and under MW irradiation. The reactions are clean, high yielding, stereoselective and compatible with environmentally friendly synthetic methodology (aqueous solution and no toxic ligands).